Exploration of Ghanaian radiographers' reporting of suspected physical abuse amongst children. Issue 3 (August 2021) - Antwi, W.K.; Reeves, P.J.; Ferris, C.; Aziato, L.
Abstract: Introduction: The success of the child protection process is dependent on rapid actions by healthcare professionals who encounter a child in possible need of protection and make appropriate referrals to statutory agencies. Clear rules that promote inter-professional working among health professionals is necessary to enhance child protection. Aim: To explore the internal factors leading to bystander attitude towards reporting of suspected physical abuse amongst Ghanaian radiographers. Methods: Twenty radiographers across Ghana who have encountered suspected child physical abuse during practice interviewed. Data was collected using qualitative methodology using semi-structured interviews. Participants were radiographers who were selected using purposive sampling. Data was thematically analysed and managed with NVivo version 10. Themes developed formed the basis of the discussion. Results: Participants reported barriers such as training deficits, lack of knowledge in reporting regulations, and the absence of a framework or structures in place to guide suspected physical abuse (SPA) management. The results showed that the majority of participants were ignorant of the role of the social worker in identified cases of SPA. Additionally, there was no teamwork in the majority of the hospitals in the management of suspected physical abuse. Conclusions: Participants' behaviour towards child protection was congruent with the situation where an individual would assess the consequences of an action. Fear, lack of direction and collaboration characterised the management of suspected physical abuse. Implication for practice: The timely identification of child abuse is key to providing the necessary intervention for the child. However, the mere identification of abuse would be of no use to the child when no action was taken by radiographers handling the case as a result of impediments on their way.